1.
a) (3-2x) - (x+4) - (2x+5) = (3x-4) - (5x+7)
b) (4-x) - (2x+3) + (x-4) = -(2x-3) - (x+ 7)
c) (4x-5) + (x-7) - (2x-8) = (-3x + 4) - (x-6)
d) - (4-2x) - (2x+4) = (3x-1 ) + (2x-5) - (7-3x)
2.
a) 2(x-7) -3(x+2) = 4(x+3) +2(x-9)
b) -3(x+6) -6(2x+8) = -2(4-x) +9(x+8)
c) -8(x+2) +3(x+5) = -2(2x+3) 4(2x-1)
d) 6(4-x) +5(2x-5) = 4(x-1) -3(4-x)

1

Odpowiedzi

2009-04-09T09:53:18+02:00
Jaki znak jest w przykładzie c 2 o tu -2(2x+3) 4(2x-1)
odpisz szybko



1
a) (3-2x) - (x+4) - (2x+5) = (3x-4) - (5x+7)
3x - 2x-x-4-2x-5= 3x-4-5x-7
3x - 2x-x-2x-3x-5x= -4-7+4+5
0≠2

b) (4-x) - (2x+3) + (x-4) = -(2x-3) - (x+ 7)
4-x-2x-3+x-4= -2x+3-x-7
-x-2x+x+2x+x= 3-7-4+4+3
x= (-7)

c) (4x-5) + (x-7) - (2x-8) = (-3x + 4) - (x-6)
4x-5+x-7-2x+8=-3x+4-x+6
4x+x-2x+3x+x= 4+6+5+7-8
7x=14 /:7
x=2

d) - (4-2x) - (2x+4) = (3x-1 ) + (2x-5) - (7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
2x-2x-3x-2x-3x=-1-5-7+4+4
-8x=5 /:(-8)
x= (-5/8)

2.
a) 2(x-7) -3(x+2) = 4(x+3) +2(x-9)
2x-14-3x-6=4x+12+2x-18
2x-3x-4x-2x=12-18+14+6
-7x=14 /:(-7)
x= -2

b) -3(x+6) -6(2x+8) = -2(4-x) +9(x+8)
-3x-18-12x-48=-8+2x+9x+72
-3x-12x-2x-9x=-8+72+18+48
-26x=130 /:(-26)
x= -5

d) 6(4-x) +5(2x-5) = 4(x-1) -3(4-x)
24-6x+10x-25=4x-4-12+3x
-6x+10x-4x-3x= -4-12-24+25
-3x=15 /(-3)
x= -5